A new species of Salina (Collembola: Paronellidae) from Anhui Province, China - Ma, Yitong (Zootaxa, 2012)
The genus Salina was established by MacGillivray (1894) with Salina banksi from the U.S.A as its type species. The main characters of the genus include: (1) absence of scales; (2) the presence of distal vesicle on dens; (3) mucro square or rectangular; (4) unpaired vertical macrosetae (Vo) absent (Mitra 1993). About 70 species have been described worldwide divided between three subgenera: Salina (s. s.) Macgillivray, Narisa Yosii & Suhardjono, 1992 and Silana Yosii & Suhardjono, 1992. The differences between these three subgenera are the number of prelabral setae and the shape of basal seta on outer maxillary lobe.